EXTERNAL MIGRATION OF HIGHER EDUCATED UNEMPLOYED: THE ROMANIAN CASE - Daniela-Emanuela Dănăcică (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2020)
The aim of this research is to portray the Romanian higher educated unemployed, who decide to leave unemployment and migrate abroad, for less or more than 3 months. 678 unemployment spells, of individuals with a higher education, registered as unemployed at the National Employment Agency and who decided to leave the country between January 1st, 2017-June 30th 2019 are analyzed. Higher educated unemployed are the social group most prone to migration, Romania currently having serious problems with the migration of highly skilled labor force.